Islam and Chinese society
1 online resource
Keywords: "This book explores the long history in China of Chinese Muslims, known as the Hui people, and regarded as a minority, though in fact they are distinguished by religion rather than ethnicity. It shows how over time Chinese Muslims adopted Chinese practices as these evolved in wider Chinese society, practices such as constructing and recording patrilinear lineages, spreading genealogies, and propagating education and Confucian teaching, in the case of the Hui through the use of Chinese texts in the teaching of Islam at mosques. The book also examines much else, including the system of certification of mosques, the development of Sufi orders, the cultural adaptation of Islam at the local level, and relations between Islam and Confucianism, between the state and local communities, and between the educated Muslim elite and the Confucian literati. Overall, the book shows how extensively Chinese Muslims have been deeply integrated within a multi-cultural Chinese society"--